The Effects Of Neurotherapy (Nft) Using Ayatul Kursi As Stimulus On Memory Performance - Norsiah, Fauzan; Nurul Amira, Abidin (Global Academic Excellence, 2017)
The purpose of the study was to assess the effectiveness of Ayatul Kursi with neurofeedback training (NFT) on memory performance among year two counseling students. In the first phase of the study, pre-test instrument Intelligence Scale Weshler Bellover, the Digit Span and Digit Symbol were administered to measure memory performance of subjects before the Neurofeedback training. A total number of 10 participants went through the pre -test on the same day in a quiet room without any interference in a counseling room. The participants went through neurofeedback training using Ayatul kursi and alpha training protocol with bipolar electrode placement on the frontal lobe (FP1 and Fp2), an executive function area with attention and judiciary (judgement) as goals for the training. Each participant was trained for five sessions for once a week at the counseling laboratory. Majority showed increased alpha wave at each session based on the data obtained. In the third phase, the post-test was carried out where instrument Intelligence Scale Weshler Bellover the Digit Span and Digit Symbol were administered after the five-training session to see the difference of scores were obtained at pre-test and the post tests. The results showed significant improvements on scores obtained by the participants.